Japan : Financial Sector Assessment Program-Detailed Assessment of Observance on Basel Core Principles for Effective Banking Supervision. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2017)
This report assesses the observance of Basel Core Principles for Effective Banking Supervision in Japan. Banking regulations and supervisory processes have undergone significant improvements since the last Financial Sector Assessment Program. The Japan Financial Services Agency is in the process of reforming its supervisory practices and has been shifting its focus from assessing compliance with prudential requirements to a more sophisticated and forward-looking risk-based approach to supervising banks and bank holding companies. Although the supervisory framework is generally sound, some key priority areas need to be addressed. Corporate governance and risk management remains an area that needs further work to strengthen independence of boards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet